1965
DOI: 10.1007/bf03004410
|View full text |Cite
|
Sign up to set email alerts
|

Succinylcholine and acetazolamide (Diamox) in anaesthesia for ocular surgery

Abstract: SUCCINYLCrIOLINE IS the muscle rel~xant of choice for tracheal mtubatlon, and tracheal mtubahon is a reqmslte for a satisfactory general anaesthesm m mtraocular surgery However, succmylchohne is known to increase mtraoeular tension In 1955 and 1957 there were reports m the hterature of loss of vitreous occurring during surgery of the open eye when succmylchohne was used m anaesthesia, x,~ with a resultmg loss of vision Succmylchohne also represented a serious hazard to patients wah glaucoma s-7A study was unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1965
1965
1988
1988

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…It has been shown that acetazolamide increases choroidal blood flow by up to three times. This drug has previously been claimed to prevent suxamethoniuminduced rise of intraocular pressure, though the mechanism is obscure (Carballo, 1965). It seems likely that acetazolamide may in fact produce an increase in TOP itself, after which the effect of suxamethonium is attenuated (Holloway, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that acetazolamide increases choroidal blood flow by up to three times. This drug has previously been claimed to prevent suxamethoniuminduced rise of intraocular pressure, though the mechanism is obscure (Carballo, 1965). It seems likely that acetazolamide may in fact produce an increase in TOP itself, after which the effect of suxamethonium is attenuated (Holloway, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The most important factor determining the internal pressure of the eye is the aqueous humour, the hydrostatic pressure of the blood accounting for only one-quarter of the total resting intraocular tension (Carballo 1965). The aqueous, which is formed by the ciliary process under the influence of carbonic anhydrase passes into the posterior chamber, through the pupil into the anterior chamber, and leaves the eye by way of the canal of Schlemm (Figure 2).…”
Section: The Gastro-intestinal Tract-intragastric Pressurementioning
confidence: 99%
“…The cannula is usually attached to a transducerpen-recorder system. This method gives a direct, continuous recording but because of the invasive nature of the monitoring it has only been used in animal experiments, and is considered unsuitable for use in man (Lincoff , Dillon et al 1957b, Wretland and Wahlin 1958, Carballo 1965, Adams and Barnett 1966. Tonometry must be considered an inferior form of measurement to manometry.…”
Section: The Gastro-intestinal Tract-intragastric Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Thus administration of an opiate as premedicant can, according to CarbaUo (1965), depress IOP by as much as 10%. There is doubt as to whether fentanyl has any effect although in high doses fentanyl can lead to a rise in lOP (Henschel, 1975).…”
mentioning
confidence: 99%